2007
DOI: 10.1007/s00127-007-0256-2
|View full text |Cite
|
Sign up to set email alerts
|

Is the prevalence of psychiatric disorders associated with urbanization?

Abstract: j Abstract Objectives In many countries, the total rate of psychiatric disorders tends to be higher in urban areas than in rural areas. The relevance of this phenomenon is that it may help in identifying environmental factors that are important in the pathogenesis of mental disorders. Moreover, urban preponderance suggests that the allocation of funds and services should take urbanization levels into account. Method The Netherlands Mental Health Survey and Incidence Study (NEMESIS) used the Composite Internati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
52
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 24 publications
(31 reference statements)
12
52
0
3
Order By: Relevance
“…The higher frequency of mental disorders for the female gender than for male gender shown in this study is in accordance with consistent findings from population samples for affective disorders and anxiety (Alonso et al, 2004;Bijl et al, 1998;Lindeman et al, 2000;Hodiamont et al, 1987;Offord et al, 1996;Bijl et al, 2002;Peen et al, 2007;Jenkins et al, 1997;Bebbington et al, 2003;Akhtar-Danesh & Landeen, 2007;Kessler et al, 1994). The opposite for alcohol and drug dependence was also in agreement with other studies.…”
Section: Comparison With Other Studiessupporting
confidence: 93%
See 2 more Smart Citations
“…The higher frequency of mental disorders for the female gender than for male gender shown in this study is in accordance with consistent findings from population samples for affective disorders and anxiety (Alonso et al, 2004;Bijl et al, 1998;Lindeman et al, 2000;Hodiamont et al, 1987;Offord et al, 1996;Bijl et al, 2002;Peen et al, 2007;Jenkins et al, 1997;Bebbington et al, 2003;Akhtar-Danesh & Landeen, 2007;Kessler et al, 1994). The opposite for alcohol and drug dependence was also in agreement with other studies.…”
Section: Comparison With Other Studiessupporting
confidence: 93%
“…The high frequency of mental disorders for individuals aged below 40 years as well as the trend of decreasing frequencies of mental disorders with older age as found in this study was also in accordance with the majority of other studies (Alonso et al, 2004;Bijl et al, 1998;Lindeman et al, 2000;Offord et al, 1996;Bijl et al, 2002;Bebbington et al, 2003;Akhtar-Danesh & Landeen, 2007;Kessler et al, 1994). Several population studies have shown higher frequencies of mental disorders with increasing urbanity (Bijl et al, 1998;Hodiamont et al, 1987;Peen et al, 2007;Jenkins et al, 1997). This trend was verified in the present study as well.…”
Section: Comparison With Other Studiessupporting
confidence: 93%
See 1 more Smart Citation
“…Due to difficulties finding providers, many patients in rural areas may resist seeing a doctor until they are severely sick (Goldsmith et al 1997), even though a lower prevalence and incidence of psychiatric disorders are noted in rural versus urban areas (Peen et al 2007). Rural residency, therefore, influences the use of psychiatric care through its contextual effects on the occurrence and severity of psychiatric illness.…”
Section: Introductionmentioning
confidence: 99%
“…Given the scarce body of literature on this subject, such results need to be interpreted with caution, without neglecting the possible indirect effects of variables such as educational attainment, occupational status, income, access to health services, among others. Several studies have identified rural-urban disparities in psychiatric disorders and quality of life (Peen et al, 2007(Peen et al, , 2010. Among a Portuguese adolescent sample, Fernandes and Vasconcelos-Raposo (2008) found that urban residents reported higher scores for personal growth, purpose in life, self-acceptance and total well-being.…”
Section: The Effects Of Sociodemographic Factorsmentioning
confidence: 99%